Design Micro-Hydro Power Plant Water Resources System for Small Medium Enterprise Rice Mill in Nagari Kamang Hilia Agam - Sandra, Nevy; Arifin, Ari Syaiful Rahman; Arbi, Yaumal; Rifwan, Fitra; Mirshad, Emilham; Zuwida, Nidal (Universitas Negeri Padang, 2024)
Processing rice products into rice requires further processing, where the grain harvested from farmers is processed into rice. The Nagari Binaan Community Service team from Padang State University will later develop this process. Farmer groups say that the availability of continuous and cheap electricity is their obstacle in producing good and cheap rice products. Counseling and assistance in making civil buildings capture turbulence water micro-hydro power plants is a solution to partner problems offered by the community service team of the Nagari program assisted by Padang State University. The output of the Nagari Fostered Program will be used to build a 5000-watt capacity power plant, supporting the need for free and environmentally friendly electricity. This aligns with the government's renewable energy program for 2030, which aims to produce 25% of the national electricity from renewable sources. This program is planned for 3 (three) stages, where the first year is mapping and detailed engineering design in the form of reports and design drawings. The second year is in the form of civil construction, and the third year's target is the installation of electrical machines and panels for commissioning. There will be training for partners, such as farmers in Kanagarian Kamang Hilia, Agam.